Low-temperature fabrication of plasmonic titanium nitride thin films by electron beam evaporation - Anindita Das; Yoshiko Nanao; Akhil Rajan; Andrea Di Falco; Sebastian A Schulz (JPhys Photonics)
Titanium nitride (TiN) is a refractory metal nitride compound with the potential to function as an alternative plasmonic material to gold, especially for high-power linear and nonlinear applications such as materials processing, telecommunications, and laser systems. This paper presents a simple, electron beam evaporation based deposition process to fabricate sub-100 nm TiN thin films at low temperatures. The dependence of optical properties and film thickness on deposition temperature was explored and it was observed that low-temperature annealing during deposition further enhances the plasmonic properties of the films. These results are essential for promoting the utilisation of highly metallic TiN thin films in plasmonic and photonic applications.